Utilização do método Multicritério AHP, na aquisição de um sistema ERP - Fernandes, José António Nascimento (2014)
The selection of an Enterprise Resource Planning (ERP) system is one of the most sensitive and highest impact processes in the area of information systems and technologies, because it supports and integrates the whole business of an organization. Hence the importance of deciding the best solution in order to contribute to the organization's competitiveness in a global and increasingly demanding market. Therefore, it is essential to provide tools to support decision making, turning complex and often intangible decisions into simple and quantifiable scenarios. This study addressed the adoption of the Analytical Hierarchy Process (AHP) multicriteria decision method to support the selection of an ERP system. The literature review was the source used to obtain the set of the most relevant criteria to be considered in this decision, which were subsequently validated through systematic application of various surveys of experts and people related to the field of ERP systems. To support the application of AHP, according to the model obtained in the study, it was developed a web application that will be available to the general public. The responsible for the acquisition of ERP systems can use it to easily apply the AHP method based on validated decision model. On the other hand, the web application can be used as a validation tool, allowing collecting data for future developments of the decision model.